Monitoring and evaluation based on results in the processes of registration of the Universal Registration System of the UNMSM - Narciso Gómez, Kennedy (2018)
The deliverable value of this research is to propose monitoring and evaluation based on results in the registration processes of the SUM-UNMSM, considering the institutional strategic plan 2017-2019 of the UNMSM, approved by Rectoral Resolution No. 001174-R-17 of January 13, 2017, which requires a coherent political leadership and a strong technical will, the opposite is to continue with routine actions that cause dissatisfaction in services to students and parents. The objective is to propose value-based procedures in the monitoring and evaluation based on results in the enrollment processes of the SUM.